J. Mod. Sim. Mater. 2018
DOI: 10.21467/jmsm.1.1.8-15
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Stiffness and Parametric Modelling of XY Flexure Mechanism for Precision Applications

Abstract: In miniaturized scale electro-mechanical framework (MEMS) flexural instruments are generally utilized in light of their preferences, frictionless and wear less movement and high accuracy. Flexures rely upon material versatility for their usefulness. In flexure component, movement is created because of flexibility of the shaft from which it is made. One of the run of the mill favorable circumstances of flexural system is to increase exact twisting and adaptability to acquire movement wanted way. This paper mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Surface roughness is also crucial, as it can affect frictional resistance and the fatigue strength of machined components. In the context of turned components, achieving a superior surface finish is important as it reduces the need for additional machining [11]. Numerous researchers have observed that surface roughness affects heat transmission during machining, the ability to retain lubricants, surface friction, and wear, among other factors.…”
Section: Fig 1 -Turning Operation With Parametersmentioning
confidence: 99%
“…Surface roughness is also crucial, as it can affect frictional resistance and the fatigue strength of machined components. In the context of turned components, achieving a superior surface finish is important as it reduces the need for additional machining [11]. Numerous researchers have observed that surface roughness affects heat transmission during machining, the ability to retain lubricants, surface friction, and wear, among other factors.…”
Section: Fig 1 -Turning Operation With Parametersmentioning
confidence: 99%
“…However, certain drawbacks exist, including fiber degradation over prolonged storage periods, moisture absorption, propensity for aggregation during processing, relatively low thermal stability, and diminished resistance to moisture [12][13][14][15]. Materials, whether natural or synthetic such as ceramics, glass, metals, meta-materials, and plastics, form the building blocks of composite materials, which represent an advanced category of materials [16][17][18]. These composites amalgamate materials with disparate physical or chemical properties to generate novel characteristics while retaining the distinct identities of the constituent materials.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, the critical design parameter is task space stiffness, which must be carefully designed to prevent undesired motion in the presence of external loads. [15][16][17]. This type of mechanism, which employs flexible segments, simplifies design by removing several stiff parts, pin joints, and additional springs.…”
Section: Introductionmentioning
confidence: 99%